2017
DOI: 10.15587/1729-4061.2017.106803
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plasticizer effectiveness during alkaline cement structure formation

Abstract: Проаналізовано проблему пластифікації цементів, лужне середовище яких визначає при-сутність сполук лужних металів, та запропоно-вано шляхи її вирішення. В якості альтернативи суперпластифікаторам на основі складних поліе-фірів запропоновано широке коло поверхнево-ак-тивних речовин, придатних для пластифікації лужних цементів. Органічні сполуки системати-зовані за ефективністю дії як пластифікатори лужних цементів Ключові слова: лужний цемент, хімічна добав-ка, поверхнево-активна речовина, гранульований доменни… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
2
10
0
2
Order By: Relevance
“…This makes it possible to reduce cement shrinkage deformation due to the falling pressure in capillaries and slowing down rate of moisture evaporation. Since most of surfactants are ineffective in a hydration medium of AAC, principles of their selection were proposed for such cements according to the criteria of variation of plastic strength [13], stability of molecular structure of admixtures having plasticizing [21] and other types of action [22] in a high alkaline medium. In this regard, it has been shown that maximum plasticizing effect is enabled by addition of sodium lignosulfonate [23], sodium gluconate [24], polyatomic alcohols and other acyclic low-and high-molecular compounds [13].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it possible to reduce cement shrinkage deformation due to the falling pressure in capillaries and slowing down rate of moisture evaporation. Since most of surfactants are ineffective in a hydration medium of AAC, principles of their selection were proposed for such cements according to the criteria of variation of plastic strength [13], stability of molecular structure of admixtures having plasticizing [21] and other types of action [22] in a high alkaline medium. In this regard, it has been shown that maximum plasticizing effect is enabled by addition of sodium lignosulfonate [23], sodium gluconate [24], polyatomic alcohols and other acyclic low-and high-molecular compounds [13].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Alkali metal compounds in such cements are considered as structure-forming components whose content depends on the AAC type. Increase in GBS content and, accordingly, alkaline component in AAC causes increase in content of the gel phase and, hence, higher shrinkage deformations [13]. This is explained by growth of the role of breakage of covalent bonds (Si-O-Si, Si-O-Al, Al-O-Al), withdrawal of anions from the polycondensation reaction and their transition into a colloidal phase in presence of alkali metal cations [11].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of creating modified concretes and mortars involves the use of multicomponent cements with a high content of SCMs and optimization of their component composition and particle size distribution due to the combination of mineral components of natural and man-made origin, nanoadditives and alkaline activation [14][15][16][17]. This will facilitate the acceleration of hydraulic and pozzolanic reactions in the SCMs system; improving the transition zone between the cement matrix and the aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…На сьогоднішній день визначено ряд ефективних типів ПАР як модифікуючих добавок для бетонів і розчинів на основі традиційних портландцементів [19,20]. Однак, більшість таких ПАР є неефективними в гідратаційному середовищі ШЛЦ, в зв'язку з чим запропоновано принципи їх вибору [21][22][23]. В цьому напрямку показано, що максимальний пластифікуючий ефект забезпечується добавками лігносульфонату натрію [24], глюконату натрію [25], багатоатомних спиртів [26] та іншими ациклічними низько-і високомолекулярними сполуками [27].…”
unclassified